Pengaruh Harga dan Iklan Terhadap Keputusan Pembelian Pada Marketplace Shopee - Sarjita Sarjita (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
This study aims to determine the effect of price and advertising together or partially on purchasing decisions in the Shopee marketplace. The research method used in this study is a quantitative research method using a sample of 70 respondents. The data analysis method used in this research is multiple linear regression. Based on the results of the t-test, it can be seen that the advertising variable has a significant effect on purchasing decisions, while price does not significantly affect purchasing decisions. Based on the beta test, the most dominant variable influencing purchasing decisions is the advertising variable. The value of the correlation coefficient (R) in this study is 0.795, meaning that the correlation test shows a strong and positive relationship, that is, if the independent variables (advertising and price) increase, the dependent variable (purchase decisions) will also increase. The value (R2) in this study was 0.632. This shows that 63.2% of purchasing decisions are influenced by price variables (X1) and advertising (X2). While the remaining 36.8% is influenced by other variables not examined in this study. Keywords: Product, Price, Place, Promotion and Sales